2019
DOI: 10.1534/g3.119.400345
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing Reveals Increased Anti-oxidant Response and Ecdysone Signaling in STAT Supercompetitors in Drosophila

Abstract: Cell competition is the elimination of one viable population of cells (the losers) by a neighboring fitter population (the winners) and was discovered by studies in the Drosophila melanogaster wing imaginal disc. Supercompetition is a process in which cells with elevated JAK/STAT signaling or increased Myc become winners and outcompete wild-type neighbors. To identify the genes that are differentially regulated in STAT supercompetitors, we purified these cells from Drosophila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 90 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…Among the conditions we re-analyzed, dilp8 induction was consistently very strong, with the exception of the ph tumors, ranging from 3.23-fold in Ras V12 + scrib- leg discs to an over 1000-fold induction in Ras V12 + scrib- wing discs ( Figure 1 ). dilp8 is a verified Yki/Sd target gene, but it can also be induced by JNK or JAK/STAT activation [ 63 , 64 , 65 ]. Notably, in cases where Yki is not activated, such as in Psc-Su(z)2 mutants, dilp8 is still heavily induced, showing that it can be induced independently of Yki activation ( Figure 1 ).…”
Section: Analysis/resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the conditions we re-analyzed, dilp8 induction was consistently very strong, with the exception of the ph tumors, ranging from 3.23-fold in Ras V12 + scrib- leg discs to an over 1000-fold induction in Ras V12 + scrib- wing discs ( Figure 1 ). dilp8 is a verified Yki/Sd target gene, but it can also be induced by JNK or JAK/STAT activation [ 63 , 64 , 65 ]. Notably, in cases where Yki is not activated, such as in Psc-Su(z)2 mutants, dilp8 is still heavily induced, showing that it can be induced independently of Yki activation ( Figure 1 ).…”
Section: Analysis/resultsmentioning
confidence: 99%
“…JAK/STAT activity can be assessed by expression of its best studied target gene, Suppressor of Cytokine Signaling at 36E (Socs36E) in various contexts [42,65,[102][103][104]. Socs36E acts as a feedback inhibitor of the pathway and can be used to test the contribution of JAK/STAT activity to tumors.…”
Section: Jak/stat Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Second, ChIP-seq experiments in Drosophila embryonic Kc cells have shown that Myc does indeed bind to the chinmo locus [79]. Finally, chinmo levels are upregulated in response to elevated Myc expression in wing imaginal discs [80]. To determine whether chinmo expression was altered in brat 1 /+ wing discs, we immunostained for Chinmo protein.…”
Section: Loss Of Cell-fate Specification May Be Due To Misregulation ...mentioning
confidence: 99%